Improvement of microstructure and mechanical properties of high dense SiC ceramics manufactured by high-speed hot pressing - Voyevodin, V.; Sayenko, S.; Lobach, K.; Tarasov, R.; Zykova, A.; Svitlychnyi, Ye.; Surkov, A.; Abelentsev, V.; Ghaemi, H.; Szkodo, M.; Gajowiec, G.; Kmiec, M.; et al. (Вопросы атомной науки и техники, 2017)
Non-oxide ceramics possess high physical-mechanical properties, corrosion and radiation resistance, which can be used as a protective materials for radioactive wastes disposal. The aim of the present study was the manufacturing of high density SiC ceramics with advanced physical and mechanical parameters. The high performance on the properties of produced ceramics was determined by the dense and monolithic structure. The densified silicon carbide samples possessed good mechanical strength, with a high Vickers micro hardness up to 28.5 GPa. Безкисневі керамічні матеріали демонструють високі фізико-механічні властивості, корозійну та радіаційну стійкість, що роблять їх перспективними кандидатами для використання в якості бар'єрних матеріалів для захоронення радіоактивних відходів. Метою цієї роботи було отримання високощільної SiC-кераміки з вдосконаленими фізичними і механічними властивостями. Високі параметри отриманої кераміки визначаються формуванням високощільної і монолітної структури. Кераміка карбіду кремнію має поліпшену механічну міцність і високу твердість по Віккерсу порядка 28,5 ГПa. Бескислородные керамические материалы демонстрируют высокие физико-механические свойства, коррозионную и радиационную стойкость, делающие их перспективными кандидатами для использования в качестве барьерных материалов для захоронения радиоактивных отходов. Целью настоящей работы было получение высокоплотной SiC-керамики с усовершенствованными физическими и механическими свойствами. Высокие параметры полученной керамики определяются формированием высокоплотной и монолитной структуры. Керамика карбида кремния обладает улучшенной механической прочностью и высокой твердостью по Виккерсу порядка 28,5 ГПa.